Search for the highly suppressed decays B- -> K+pi(-)pi(-) and B- -> K-K-pi(+) - Aubert, B; Bona, M; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Garra Tico, J; Grauges, E; Lopez, L; Palano, A; et al. (2008)
We report a search for the decays B -→K+π-π- and B -→K-K-π+, which are highly suppressed in the standard model. Using a sample of (467±5)×106 BB̄ pairs collected with the BABAR detector, we do not see any evidence of these decays and determine 90% confidence level upper limits of B(B -→K+π-π-)<9. 5×10-7 and B(B-→K-K -π+)<1.6×10-7 on the corresponding branching fractions, including systematic uncertainties. © 2008 The American Physical Society.